SOCIO-DEMOGRAPHIC DETERMINANTS OF HUMAN DEVELOPMENT IN NIGERIA: A PANEL DATA ANALYSIS - Kuhe, David Adugh; Aniah-Betiang, Elizabeth Ishagba; Uba, Tersoo; Onuche, Peter (FUDMA Journal of Sciences, 2026)
This study examined the socio-demographic determinants of human development in Nigeria using panel data covering the six geopolitical zones over the period 1994-2024. Despite the growing body of literature on human development, existing studies in Nigeria have largely relied on time-series or cross-sectional approaches, focused on isolated demographic indicators, and paid limited attention to the dynamic long-run and causal interactions between socio-demographic factors and human development. To address this gap, this study integrated Dynamic Fully Modified Ordinary Least Squares (FMOLS), Panel Vector Error Correction Model (PVECM), and Dumitrescu-Hurlin panel causality techniques within a unified panel econometric framework. The Human Development Index (HDI) was modeled as a function of life expectancy at birth, population growth, fertility rate, maternal mortality rate, urbanization rate, population density, female labour force participation, dependency ratio, and youth population using a balanced panel comprising 180 observations across six geopolitical zones from 1994 to 2024. Panel unit root tests (LLC and CADF/CIPS) confirmed that all variables were integrated of order one, while the Johansen Fisher panel cointegration test established the existence of long-run equilibrium relationships among the variables. FMOLS estimates revealed that life expectancy (β = 0.2146), urbanization (β = 0.3261), female labour force participation (β = 0.2357), and youth population (β = 0.3149) significantly enhanced human development. Conversely, population growth (β = –0.1365), fertility rate (β = –0.4509), maternal mortality rate (β = –0.4933), dependency ratio (β = –0.0709), and population density (β = –0.0385) exerted significant negative effects on HDI.
Keywords: Human Development Index; Panel Cointegration; Panel Vector Error Correction Model; Panel Granger Causality; Nigeria